Influence Of Fuel Injection Techniques On Combustion Performance Of Multi-Jet Shear Layer Combustion - Mustafa, A.; Andrews, G. E. (2003)

(untitled)
Experimental work was carried out to study the effect of fuel injection techniques on the high intensity non-swirl multi-jet shear layer combustion performance of a fourhole conical burner. Two modes of gas oil fuel injection were investigated using a simple type atomiser with four holes positioned 45o to the horizontal axis and can be manually aligned either offset or inline with the hole centre. This enables the fuel to be radially injected either straight into or between the jet shear layers. The test results show that the fuel injection techniques had strong influence on the fuel atomisation and the fuel/air mixing and hence the combustion performance. The NOx results of the offset fuel injection showed a typical NOx profile of an aerodynamic lean/rich combustion. The inline fuel injection produced better combustion performance as compared to the offset injection but was limited by a narrower stability. However, the relatively high combustion inefficiency , as indicated by high CO and UHC emissions, with the inline injection mode even though at high pressure losses indicate the problems of inadequate atomisation and mixing which were attributed mainly to the aerodynamic features of the system concerned.